Prediction of signal recognition particle RNA genes. - Regalia, M.; Rosenblad, M.A.; Samuelsson, T. (Nucleic Acids Research, 2002)
We describe a method for prediction of genes that encode the RNA component of the signal recognition particle (SRP). A heuristic search for the strongly conserved helix 8 motif of SRP RNA is combined with covariance models that are based on previously known SRP RNA sequences. By screening available genomic sequences we have identified a large number of novel SRP RNA genes and we can account for at least one gene in every genome that has been completely sequenced. Novel bacterial RNAs include that of Thermotoga maritima, which, unlike all other non-gram-positive eubacteria, is predicted to have an Alu domain. We have also found the RNAs of Lactococcus lactis and Staphylococcus to have an unusual UGAC tetraloop in helix 8 instead of the normal GNRA sequence. An investigation of yeast RNAs reveals conserved sequence elements of the Alu domain that aid in the analysis of these RNAs. Analysis of the human genome reveals only two likely genes, both on chromosome 14. Our method for SRP RNA gene prediction is the first convenient tool for this task and should be useful in genome annotation.